Nanoestruturas de GaN crescidas pelas técnicas de epitaxia por magnetron sputtering e epitaxia por feixe molecular - Schiaber, Ziani de Souza [UNESP] (2016)
GaN nanowires and nanocolumns stand out due to the low defect density and high structural and optical quality compared to the corresponding thin films. The understanding of the formation mechanism of the different GaN structures using different techniques is critical to improving the manufacture of the electronic and optoelectronic devices based on this material. This thesis focuses on the preparation and characterization of GaN nanowires and nanostructures. The molecular bem epitaxy (MBE) and magnetron sputtering epitaxy (MSE) were used and different substrates were tested. Concerning GaN nanocrystals and nanocolumns obtained by MSE, optimization of the deposition conditions was necessary in order to produce non-coalesced GaN nanostructures. The best conditions were: pure N2 atmosphere, silicon substrate, and a perforated screen placed between the target and the substrate holder. The later produced differences on the Ga flow to the substrate, inducing the formation of different structures, depending on the position of growth spot. Samples were characterized using scanning electron microscopy, X-ray diffraction and photoluminescence spectroscopy. Nanocolumns were observed, mainly in sites corresponding to a disc of radius 2 mm from the geometric centre of the hole. The columns were oriented with the GaN [001] axis perpendicular to the Si (111) substrate surface, situation which is commonly found in GaN nanowires deposited by MBE. Regarding the nanowires prepared by MBE technique, in order to inhibit coalescence and to investigate the possibility of controlling the numerical density of nanowires, we have used Si cap layers on top of the Ga-polar GaN buffer layer. Different amounts of Si have been deposited, and the density of the nanowires was significantly modified. With Si layer thickness of 0.60 nm, the nanowires had an average density of 108 nanowires/cm2 . Lower thickness did not result in the growth of nanowires, but higher thickness caused a high density of nanowires of 1010 nanowires/cm2 which remained constant regardless of the deposition time. X-ray diffraction pole figures showed that the different nanowires grown up in oriented fashion in a crystalline layer of Si or SixNy. Etching with KOH indicated N polarity for the grown nanowires, in spite of the fact that they were grown using Ga polar GaN buffer layers. Measurements by convergent beam electron diffraction confirmed the N polarity to the nanowire and Ga polarity for the buffer layer. Aspects obtained in this study allowed a better understanding of nucleation and nanostructures formation mechanisms of GaN, enabling greater control of the characteristics of these nanostructures produced.